Using Tasseled Cap Transformation of CBERS-02 Images to Detect Dieback or Dead Robinia Pseudoacacia Plantation - Qingsheng Liu; Gaohuan Liu (2009 2nd International Congress on Image and Signal Processing, 2009)
Brightness, Greenness, and Third component tasseled cap transformation parameters for the four bands of CBERS-02 CCD images were developed. First, the image acquired on May 9, 2005 in the Yellow River Delta was used to calculate the Brightness and Greenness and Third component tasseled cap transformation parameters. Then use the parameters to calculate the Brightness and Greenness of four images acquired from March 18, April 13, May 9 and June 6, 2005. The Brightness versus Greenness in this paper resembles other scholars' results of other sensors in shapes. Finally, use Greenness change difference map among multi-date CBERS-02 CCD images and Decision tree to detect dieback or dead Robinia Pseudoacacia plantation of Gudao Forestry Centre successfully. The results show that the tasseled cap transformation of multi-date CBERS-02 CCD images can be used to monitoring forest health, and now Robinia Pseudoacacia plantation of Gudao Forestry Centre is unhealthy, and needs to be managed and protected effectively.